The reality of the use of Electronic Education in the Faculty of Computer and Mathematics, University of Wassit: Wassit University - Hafith Ibraheem, Ahmed (Journal of College of Education, 2017)
: During the last quarter of the last century, university education witnessed an essential shift in teaching methods, patterns and fields of education. Many Arab and international universities tended to employ and its application in the educational process. The gool of this stady is identifying the extent to which the Faculty of Computer and Mathematics at the University of Wassit is ready to apply Electronic Education and identifying the obstacles facing the implementation and activation of Electronic Education in the University of Wasit, we suggest Providing the necessary infrastructure, material resources, and human potentials for the use of Electronic Education, through providing equipment, sites, and electronic networks and other Internet services efficiently at the university end setting up training courses for faculty members to develop their skills in how to take advantage of Electronic Education and to provide financial support to conduct research and disseminate awareness of this type of education and culture